Featured data sources and normalised indices of use in small Arctic catchments research - Wołoszyn, Aleksandra (Quaestiones Geographicae, 2024)
The development of remote sensing instruments and methods has revolutionised work practices worldwide, resulting in a new field of research. Remote sensing has significantly expanded the possibilities for detailed research, spanning from biological to urban studies, by constantly imaging the Earth. Numerous photogrammetric campaigns and satellite missions have been increasing the possibilities for conducting research that includes larger areas and time scales while minimising the need for fieldwork. This is particularly useful in polar regions, where fieldwork is complicated by harsh weather conditions, hard-to-reach research areas, polar nights, and the need for high funding and logistical support. Here available algorithms that help to track environmental shifts in the small Arctic catchments, such as changes in ice, snow, vegetation, and water are presented.